Chemical weathering rate and CO2 consumption in basaltic and sandstone cuesta landscape in São Paulo State, Brazil - de Souza Sardinha, Diego; Godoy, Letícia Hirata [UNESP]; da Conceição, Fabiano Tomazini [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
This paper quantified the chemical weathering rate and CO2 consumption in basaltic and sandstone cuesta landscape based on sodium, potassium, calcium, magnesium, and silica elements using the Jaú River, in the state of São Paulo, Brazil, as the study area. The mobility of SiO2, Na+, K+, Ca2+ and Mg2+ elements in the rock/soil system occurs in the alteration stages of potassium feldspar, albite, anorthite, augite, and anorthoclase primary minerals. The rainwater data indicate an annual deposition of 1.28 t/km-2/year for SiO2, 0.60 t/km-2/year for Ca2+, 0.43 t/km-2/year for Mg2+, 0.34 t/km-2/year for K+ and 0.27 t/km-2/year for Na+. In the river waters, the annual specific flow was calculated as 7.11 t/km-2/year for SiO2, 4.72 t/km-2/year for Ca2+, 2.33 t/km-2/year for Na+, 2.44 t/km-2/year for Mg2+ and 0.88 t/km-2/year for K+. The atmospheric/soil CO2 consumption was 0.57x106 mol.km-2/year for the Jaú River basin and when it was extrapolated to the Basaltic Cuestas geomorphological province in São Paulo State, it was estimated as 0.03x1012 mol/year, which is an important consideration to global warming. The chemical weathering rate (10 m/Ma) was compared with other studies in different geomorphological provinces in São Paulo State, which has a variation between 6 and 22 m/Ma.
Taxa de intemperismo químico e consumo de CO2 em relevo cuestiforme com substrato basáltico e arenítico no estado de São Paulo, Brasil
Keywords: Geochemistry; Hydrochemistry; Tropical region; Water/rock/soil interaction